Graffiti Virtual Exhibition “Pandemic Youth” - Donna Carollina (IJCAS (International Journal of Creative and Arts Studies), 2020)
In the middle of March 2020, Indonesia declared a Covid-19 emergency. This pandemic has an impact on art activities, including the artistic world of graffiti. During this time, the activities of graffiti artists in public spaces were increasingly limited. However, this limitation does not dampen their spirit, especially in terms of organizing exhibitions. Where on May 17, 2020, they held a virtual exhibition titled "Youth Pandemics." This topic is interesting to discuss since organizing a virtual exhibition is a new thing for graffiti artists, especially in Indonesia. This research uses the descriptive qualitative method. This study's results reveal that implementing a virtual exhibition gave new alternative space for graffiti artists during a pandemic. Also, a virtual exhibition is a place to gather for graffiti artists amid their social limitations. Pameran Virtual Graffiti “Pandemic Youth” ABSTRAK Medio Maret 2020 Indonesia dinyatakan darurat Covid-19. Pandemik ini berdampak pada aktivitas seni termasuk di dalamnya dunia artistik graffiti. Selama pandemik, aktivitas artistik pelaku graffiti di ruang publik semakin terbatas. Namun batasan ini tidak menyurutkan semangat berkesenian sebagian pelaku graffiti, terutama dalam hal penyelenggaraan pameran. Dimana pada 17 Mei 2020 lalu mereka menyelenggarakan pameran virtual bertajuk “Pandemic Youth”. Topik ini menarik untuk dibahas mengingat upaya penyelenggaraan pameran virtual ini merupakan hal yang baru bagi pelaku graffiti khususnya di Indonesia. Penelitian ini menggunakan metode kualitatif deskriptif. Hasil dari penelitian ini mengungkap bahwa penyelenggaraan pameran virtual menambah alternatif baru bagi ruang berekspresi para pelaku graffiti di tengah pandemik. Selain itu pameran virtual sekaligus menjadi wadah berkumpul bagi para pelaku graffiti di tengah keterbatasan sosial mereka.